Participatory Empowerment Of Capture Fisheries Collective Business Group (Kub) In Tungkaran Pangeran Sub-District, Tanah Bumbu Regency - Lilik Suryani; Andi Tenri Sompa; Setia Budhi (International Journal of Politic, Public Policy and Environmental Issues, 2022)
This study describes and understands the joint venture community development group (KUB) in KUB Tungkaran Prince, Tanah Bumbu, Indonesia. This research uses a descriptive qualitative approach. The research subjects are KUB managers and members. Data collection techniques were carried out using interviews, observation, and documentation. The data analysis technique used is data reduction, presentation, and conclusion drawing. The results showed that the empowerment of joint business groups (KUBE) in KUB was carried out in stages, starting from the preparation, implementation and evaluation processes and the obstacles faced, including lack of business capital and the participation of group members. KUB's supporting factors include complete tools, supporting natural resources, members marketing products and business partners. The independence of KUB has not been maximized, so it is essential to carry out a mentoring process.